2009
DOI: 10.1021/bi901496q
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and Energetics of the Base Flipping Conformation Studied with Base Pair-Mimic Nucleosides

Abstract: A base flipping conformation is found in many biological processes, including DNA repair and DNA and RNA modification processes. To investigate the dynamics and energetics of this unusual conformation in a double helix, base flipping induced by the base pair analogues of deoxyadenosine and deoxycytidine derivatives tethering a phenyl or naphthyl group was investigated. DNA strands bearing the base pair analogues stabilized the base flipping conformation of a complementary RNA, resulting in a site-specific hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…Our previous studies using the UV thermal melting curves and fluorescence spectra suggested that dA phe and dA naph introduced into a DNA sequence do not form a base pair with thymine in a complementary strand but induce base flipping (6,7). These spectroscopic measurements, however, only provide suggestive evidence for the base conformation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous studies using the UV thermal melting curves and fluorescence spectra suggested that dA phe and dA naph introduced into a DNA sequence do not form a base pair with thymine in a complementary strand but induce base flipping (6,7). These spectroscopic measurements, however, only provide suggestive evidence for the base conformation.…”
Section: Resultsmentioning
confidence: 99%
“…The 2′-deoxyadenosine and 2′-deoxycytidine derivatives shown in Figure 1A were synthesized and identified as previously described (6,7). DNA oligonucleotides containing the nucleotide derivatives and those labeled with Cyanine 3 (Cy3) at their 5′-ends were synthesized on a solid support using conventional phosphoramidite chemistry with an automated DNA synthesizer (Model 391, Applied Biosystems).…”
Section: Methodsmentioning
confidence: 99%
“…The RNA-hydrolyzing activity agrees with the base flipping model in which A X forces the opposite base to flip out in an unstacked position (Figure 6(c)). The rate of the RNA hydrolysis was relatively slow comparable to the nonspecific hydrolysis of a single-stranded RNA strand but much faster than those of the unmodified duplexes forming a mismatch pair [55]. Thus, it is likely that A X induces the base flipping of a structurally unconstrained phosphodiester bond as much as ribonucleotides in a single-stranded state.…”
Section: The Base Pair Analogs Of a Base Pair-mimic Structurementioning
confidence: 99%
“…When the deoxycytidine derivatives were investigated, the thermodynamic stability and the RNA hydrolysis data agreed with the flipping of A, C, T, or U opposite to C phe . However, the base pair through hydrogen bonding is formed between C phe and G by orienting the nonpolar aromatic group into the major groove of the duplex, rather than the guanine flipping conformation [55]. This observation is markedly different from the deoxyadenosine derivatives inability to form the base pair with T and U.…”
Section: The Base Pair Analogs Of a Base Pair-mimic Structurementioning
confidence: 99%
“…N6-Naphthylcarbamoyladenosine and N4-naphthylcarbamoylcytosine, when base paired with uracil in an RNA strand, causes the uracil base to be flipped out of the duplex resulting in hydrolysis of the uracil to generate an abasic site. 305 Various ligands have been reported that are able to bind into duplex DNA opposite an abasic site, and can therefore be used to detect the presence of the abasic site. Such ligands include (methyl-substituted) 2-amino-1,8-naphthyridines, 306 guanidinemodified naphthalenes 307 and rhodium biphenylchrysene 308 derivatives.…”
Section: Oligonucleotide Synthesismentioning
confidence: 99%